2010
DOI: 10.1029/2010gl042711
|View full text |Cite
|
Sign up to set email alerts
|

Link between EMIC waves in a plasmaspheric plume and a detached sub‐auroral proton arc with observations of Cluster and IMAGE satellites

Abstract: [1] In this paper, we report observations from a Cluster satellite showing that ULF wave occurred in the outer boundary of a plasmaspheric plume on September 4, 2005. The band of observed ULF waves is between the He + ion gyrofrequency and O + ion gyrofrequency at the equatorial plane, implying that those ULF waves can be identified as EMIC waves generated by ring current ions in the equatorial plane and strongly affected by rich cold He + ions in plasmaspheric plumes. During the interval of observed EMIC wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 43 publications
4
85
0
Order By: Relevance
“…As shown in Fig. 5a the O + ion gyrofrequency (f O + eq ) and the He + ion gyrofrequency (f He + eq ) in the equatorial plane, i.e., in frequency range for He + ion cyclotron waves in the equatorial plane, in agreement with the previous observations and theory of EMIC waves (Erlandson and Ukhorskiy, 2001;Morley et al, 2009;Yuan et al, 2010Yuan et al, , 2012aYoung et al, 1981). As shown in Fig.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…As shown in Fig. 5a the O + ion gyrofrequency (f O + eq ) and the He + ion gyrofrequency (f He + eq ) in the equatorial plane, i.e., in frequency range for He + ion cyclotron waves in the equatorial plane, in agreement with the previous observations and theory of EMIC waves (Erlandson and Ukhorskiy, 2001;Morley et al, 2009;Yuan et al, 2010Yuan et al, , 2012aYoung et al, 1981). As shown in Fig.…”
Section: Discussionsupporting
confidence: 79%
“…With density enhancements of cold ions, the anisotropic RC proton distributions can become unstable so as to easily excite EMIC waves (Gary et al, 1995). Therefore, EMIC waves in the inner magnetosphere may occur in the region of overlap between the plasmasphere and ring currents (Fraser and Nguyen, 2001;Yuan et al, 2010Yuan et al, , 2012aUsanova et al, 2013), and in regions of high cold plasma density (Yahnin et al, 2002;Halford et al, 2015). In addition, the density structure with the negative gradient of radial electron densities at the plasmapause or plasmaspheric plumes can guide EMIC waves, leading to a small wave normal angle and an order of enhancement of the wave strength (Chen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shprits et al (2013) demonstrated that EMIC waves play a crucial role for the dynamics of the ultrarelativistic populations in the radiation belts. Detached proton subauroral arcs are caused by the precipitation of ring current protons into the atmosphere produced by EMIC waves (e.g., Jordanova et al 2007;Spasojevic and Fuselier 2009;Yuan et al 2010). As EMIC waves play an important role in the dynamics of the inner magnetosphere, in this section, we consider how heavy ions regulate EMIC wave scattering, their impact on ion heating by these waves and the minimum resonant energy during wave-particle interactions.…”
Section: Scattering and Heating Of Particles By Emic Waves In The Prementioning
confidence: 99%